Lope de Vega y las fiestas de Lerma de 1617 - Manuel Cornejo (Mélanges de la Casa de Velázquez, 2007)
The object of this article is to recall to memory two virtually unknown accounts of the grand theatrical festivals organised by the Duke of Lerma in the town of that name in October 1617. In addition to the references in Lope’s letters, these two accounts –one burlesque, the other «serious» –which appear in his brilliant but little-known comedy Lo que pasa en una tarde, leave little room for doubt that Lope de Vega was present at these courtly festivities.